Molecular mechanisms of DNA repair in Mycobacterium tuberculosis - Gessner, Sophia Johanna (Division of Medical Microbiology, 2018)
The mycobacterial DNA damage and repair pathways involved in the emergence of drug-resistance during host infection remain poorly understood, yet are critical to any efforts to develop novel "anti-evolution" drugs aimed at reducing the capacity of Mycobacterium tuberculosis to adapt genetically during tuberculosis (TB) treatment. The thesis presented here aimed to investigate the contribution of the DNA damage (SOS) response in adaptive mutagenesis, and focused on two specific components: the role of the specialist translesion synthesis DNA polymerase, DnaE2, in mutagenesis under stress and, secondly, the function of the mycobacterial homologue of a putative SOS response associated peptidase (SRAP) protein which has been identified in comparative genomics analyses of organisms possessing a DnaE2-type C family DNA polymerase. This work focused on the putative SRAP protein which was predicted to form part of the mycobacterial DNA damage response as a functional switch by binding DNA in an autoproteolytic dependent manner. To this end, SRAP deletion mutants were generated for both M. smegmatis (MSMEG_1891) and M. tuberculosis (Rv3226c). Despite the fact that SRAP was upregulated in both M. smegmatis and M. tuberculosis following genotoxic stress, no DNA damage phenotype was detected in any SRAP deletion mutant using a variety of DNA damaging agents. In parallel, an eGFP-tagged M. smegmatis SRAP allele was constructed to enable visualisation of SRAP upregulation and sub-cellular recruitment using fluorescent microscopy; however no eGFP expression could be visualised after MMC treatment. It was not clear whether this was due to faulty eGFP expression in the fusion protein, or to low-level induction of SRAP. In a biochemical approach to elucidate SRAP function, soluble M. smegmatis SRAP protein was expressed and purified using a N-terminal hexa-histidine tag. No proteolytic activity was detected in gelatine or casein zymography, perhaps indicating that SRAP has a very specific substrate. Moreover, while it was predicted that autocatalytic cleavage of the C-terminus was required for activation of SRAP, no such cleavage was detected using hexa-histidine tag staining, possibly pointing to a set of very specific conditions for activation. In combination, therefore, neither microbiological nor biochemical assays could elucidate a definitive role for SRAP in the mycobacterial DNA damage response. DnaE2 has been directly implicated in induced mutagenesis to rifampicin (Rif) resistance in Mycobacterium tuberculosis following exposure of bacilli to genotoxic stress. In previous work in our group, a vitamin B₁₂-sensitive ΔmetH strain was found to form "B₁₂-resistant" suppressor mutants at a frequency higher than could be explained by spontaneous mutagenesis alone. The first part of this thesis investigated the potential role of DnaE2 in the high-frequency emergence of B₁₂-resistance by mutating DnaE2 in the ΔmetH background. Whereas elimination of polymerase function in a DnaE2ᴬᴵᴬ mutant abrogated DNA damage-induced mutagenesis to Rif resistance, no change in B₁₂ sensitivity was detected in a ΔmetH dnaE2ᴬᴵᴬ double mutant. PCR sequencing of spontaneous B₁₂-resistant mutants revealed mutations in genes previously associated with the suppressor phenotype; moreover, there was no apparent difference in the nature of mutations observed in both parental and dnaE2ᴬᴵᴬ mutant strains. Instead, these results suggest that an alternative mechanism must exist to enable adaptive mutagenesis in methionine-starved mycobacteria.